TRENDS AND BEST PRACTICES FOR ENSURING DIGITAL ACCESSIBILITY IN THE WORKPLACE - NACHEVA, Radka (Journal of process management and new technologies, 2025)
Digital accessibility in the workplace is essential for creating an inclusive environment where all employees can fully participate. Trends include AI-powered accessibility solutions, voice user interfaces (VUI), mobile accessibility, inclusive design practices, and adhering to global accessibility standards like the Web Content Accessibility Guidelines (WCAG). Inclusive design goes beyond accessibility compliance, considering diverse user needs from the start of the design process. Global accessibility standards are increasingly adopted to ensure a consistent and globally inclusive digital workplace. Best practices for promoting digital accessibility include accessibility training for all employees, active involvement of people with disabilities in user testing, creating accessible documents, choosing collaboration and communication tools, conducting regular accessibility audits, designing and maintaining internal websites and intranet platforms, establishing clear accessibility policies and guidelines, implementing employee feedback mechanisms, and ensuring leadership commitment to fostering a culture of accessibility. Organizations can create a digital workplace that is not only accessible but also promotes a more inclusive and diverse work environment. In this regard, the paper aims to explore the global trends and good practices related to digital accessibility by deriving recommendations for ensuring digital accessibility in the workplace.
Keywords: Digital accessibility; inclusive design practices; workplace accessibility